2011
DOI: 10.1002/jmri.22793
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo water diffusion tensor properties of the fibroid uterus at 7 T and their relation to tissue morphology

Abstract: Purpose: To investigate the water diffusion tensor properties of ex vivo tissue in the fibroid uterus, including the influence of degeneration, and the relevance of the principal eigenvector orientation to the underlying tissue structure. Materials and Methods:Following hysterectomy, high-resolution structural T 2 -weighted and diffusion tensor magnetic resonance imaging (DT-MRI) were performed on nine uteri at 7 T. Mean diffusivity (MD), fractional anisotropy (FA), and principal eigenvector orientation were m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…The fiber architectures visualized in our study were similar to the previous reports performed ex vivo (20,21), and in vivo (19,29) where circularly arranged fibers appeared in slices taken orthogonally to the long axis of the uterine corpus. The mean FA was highest for the JZ (0.297 6 0.033), followed by the OM (0.257 6 0.022) and EM (0.186 6 0.039).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The fiber architectures visualized in our study were similar to the previous reports performed ex vivo (20,21), and in vivo (19,29) where circularly arranged fibers appeared in slices taken orthogonally to the long axis of the uterine corpus. The mean FA was highest for the JZ (0.297 6 0.033), followed by the OM (0.257 6 0.022) and EM (0.186 6 0.039).…”
Section: Discussionsupporting
confidence: 89%
“…The fiber architectures visualized in our study were similar to the previous reports performed ex vivo , and in vivo where circularly arranged fibers appeared in slices taken orthogonally to the long axis of the uterine corpus.…”
Section: Discussionsupporting
confidence: 88%
“…Thrippleton et al (14) performed an ex vivo study with a 7T MRI and found the FA value of the leiomyomas to be around 0.20-0.28±0.053, and the myometrium as 0.395±0.032; they concluded that these findings suggest that water molecule diffusion may be fastest in a direction parallel with fibers of the myometrial muscles and dense fibroid structures (14). The differences in the FA and ADC values of the cyclic reproductive and postmenopausal endometrium are likely to determine variations in the viscosity of the interstitial space and in the ratio of the volume occupied by cells to the volume of the interstitial space.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of DWI, and DTI sequences which serve as functional imaging in the MRI protocol for the evaluation of uterine pathologies have been offered by several papers [2,3,7,8] . Besides quantitative evaluation with values has been found out to be effective in the discrimination of malignancy from benign lesions [1720] .…”
Section: Dwi and Dti Of Diseased Uterusmentioning
confidence: 99%